Accessibility of pertussis vaccine immunization services in Hubei Province from a supply–demand coupling perspective - Li, Dan; Wang, Lei; Li, Hao; Guan, Xuhua (Frontiers in Public Health, 2025)
BackgroundChina consistently ranked among the top three contributors to global pertussis cases from 2021 to 2024. However, limited research on the accessibility of pertussis vaccines from a supply–demand perspective has hindered effective control measures.MethodsA birth cohort-stratified survey was conducted in Hubei Province, China, from March to August 2024. Data on the geographical, awareness-related, and economic accessibility of pertussis vaccination services were collected using electronic questionnaires and field surveys, targeting vaccination staff (supply-side) and caregivers of eligible children (demand-side). Influencing factors were analyzed using the χ2 test and univariate and multivariate logistic regression analyses.ResultsA total of 1,350 vaccination staff members from 914 clinics and 1,098 caregivers of eligible children across 17 prefecture-level cities were surveyed. Geographically, 80% of vaccination staff members reported that their clinic’s nearest clients lived within 2 km, and 89.89% of caregivers of eligible children traveled <30 min for vaccination. Average awareness rates were 72.92% for vaccination staff and 69.90% for caregivers of eligible children (χ2 = 14.887, p < 0.05). Among vaccination staff, female individuals and those aged ≤30 years with college education, senior titles, or more than 15 years of experience showed ≥2-fold higher odds of having good awareness. Caregivers of eligible children who held a college degree, worked in medical professions, resided in urban residence, fulfilled maternal/grandmaternal roles, had an income of ≥100,000 CNY, or had infants aged ≤12 months showed 1.5–2.6-fold higher awareness. Economically, 93.11% of vaccination staff worked in clinics that provided free National Immunization Program (NIP) pertussis vaccines (DTaP), and 87.80% of caregivers of eligible children were willing to pay for non-NIP pertussis vaccines.ConclusionThe geographical and economic accessibility of pertussis vaccination services is relatively reasonable in Hubei Province, China. However, knowledge gaps still exist on both the supply and demand sides. Targeted training for older, male, or less-experienced vaccination staff, along with customized education for rural, low-income, male caregivers of eligible children, could help bridge these gaps and reduce the disease burden in China.